ANALYSIS OF THE RELATIONSHIP OF MARKETING MIX TO SALES TURNOVER AND NUMBER OF BUYERS IN THE SMALL AND MEDIUM INDUSTRIES OF SNACK FOOD PRODUCTS, CIAMIS DISTRICT - Faisal H. Batubara (Asosiasi Dosen Muda Indonesia, 2024)
The aim of this research was to investigate the correlation between marketing mix variables and both sales revenue and the number of buyers. The findings from the correlation test indicate that all marketing mix variables exhibit a significantly positive correlation with sales revenue and the number of buyers, with the exception of the promotion variable, which shows a positive correlation but lacks statistical significance in relation to sales revenue. The utilization of an effective marketing mix enables the company to boost sales revenue and attract more buyers. This is evident in the positive and statistically significant correlation observed between all marketing mix components and the increasing number of buyers, emphasizing the role of marketing strategies in enhancing corporate sales revenue. The results, with a substantial correlation coefficient of 0.499, affirm that a higher level of marketing efforts correlates with an augmented number of buyers, thereby contributing to increased sales revenue. The descriptive analysis underscores the continued significance of local and regional markets in promoting junk food products in Ciamis regency. To foster the growth of the junk food industry, there is a need to strengthen local markets, potentially by revamping traditional markets with efficient wholesale or retail facilities to enhance their appeal. Furthermore, integrating the marketing of junk food with Ciamis District as an appealing Tourism Destination Object could offer additional opportunities for the industry's development.